2019
DOI: 10.3390/rs11030228
|View full text |Cite
|
Sign up to set email alerts
|

GNSS RTK Positioning Augmented with Large LEO Constellation

Abstract: It is widely known that in real-time kinematic (RTK) solution, the convergence and ambiguity-fixed speeds are critical requirements to achieve centimeter-level positioning, especially in medium-to-long baselines. Recently, the current status of the global navigation satellite systems (GNSS) can be improved by employing low earth orbit (LEO) satellites. In this study, an initial assessment is applied for LEO constellations augmented GNSS RTK positioning, where four designed LEO constellations with different sat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Based on relationship (1), it should be concluded that, at present, the main parameter whose value can be influenced by the system user is the DOP [26][27][28][29]. Its value is determined by the following: the instantaneous location of satellites in relation to the observer, i.e., to the azimuth and the elevation, the number of satellites used to determine the position coordinates, the min.…”
Section: Drms-distancementioning
confidence: 99%
“…Based on relationship (1), it should be concluded that, at present, the main parameter whose value can be influenced by the system user is the DOP [26][27][28][29]. Its value is determined by the following: the instantaneous location of satellites in relation to the observer, i.e., to the azimuth and the elevation, the number of satellites used to determine the position coordinates, the min.…”
Section: Drms-distancementioning
confidence: 99%
“…In recent years, Global Navigation Satellite Systems (GNSS) have been used by relative or absolute methods for millimeter to centimeter level positioning. One of the relative methods, Real Time Kinematic (RTK) method which eliminates many errors by double differencing (DD) technique is extensively used in many geospatial studies (Odijk et al 2012;Yu et al 2016;El-Mowafy and Kubo 2017;Erenoglu 2017;Dabove 2019;Li et al 2019;Ogutcu 2019). The accuracy in RTK mostly depends on the distance between reference station and rover socalled -baseline length-due to the orbital errors and the changing atmospheric conditions.…”
Section: Introductionmentioning
confidence: 99%
“…2020, 12,2063 2 of 17 satellite communication channels. Some research has demonstrated that the LEO satellite signal augmentation method can dramatically reduce the convergence time of Precise Point Positioning (PPP) [8] as well as long-baseline real-time kinematic (RTK) positioning by taking the advantages of the rapid geometric change of LEO satellites [9,10]. Moreover, it also can improve the usability and reliability of the present Global Navigation Satellite System (GNSS) and supporting the Positioning Navigation Timing (PNT) systems as well as the space-based real-time Positioning, Navigation, Timing, Remote-sensing, and Communication (PNTRC) information service systems [11,12].…”
Section: Introductionmentioning
confidence: 99%